CAMELLIA PYRIFORMIS (THEACEAE, SECTION CALPANDRIA), A NEW SPECIES FROM NORTHERN VIETNAM - Trinh, Ngoc Bon (Trường Đại học Đà Lạt, 2024)
Camellia pyriformis is described, illustrated, and placed in section Calpandria. Morphological features of this new species are young branches villous; leaves above pubescent, a long midrib, below pubescent; petiole falcate, densely villous; flowers solitary or geminate; pedicel very short, pubescent; bracteoles sparsely pubescent on both sides; sepals, pubescent on both sides; petals, white, glabrous; androecium 5–6 stamens, filaments completely united to form a truncated cone, glabrous, basal adnate to the petal, shallowly dentate at the apex, each filament bearing an anther; gynoecium 3-locular, densely white silky strigose tomentose, styles glabrous; capsule pyriform, pubescent; seed broad pyriform, densely villous